Effects of tongue cleaning on Ayurvedic digestive power and oral health-related quality of life: A randomized cross-over study. (February 2018) - Tokinobu, A.; Yorifuji, T.; Sasai, M.; Doi, H.; Tsuda, T.
Highlights: A RCT to evaluate the effects of tongue cleaning on Ayurvedic digestive power and oral health-related quality of life. Tongue cleaning may be an effective method to improve Ayurvedic digestive power and oral health-related quality of life. Tongue cleaning appears to be safe and easy to practice. Abstract: Objectives: The effect of tongue cleaning on digestive power is mentioned in Ayurvedic information sources. However, no study has yet evaluated this. We aimed to evaluate the effects of tongue cleaning on digestive power from Ayurvedic viewpoint, and on oral health-related quality of life (OHRQoL) in healthy adults. Design: Randomized cross-over. Interventions: We recruited healthy adults aged 20–60 years. After randomization, the immediate intervention group started tongue cleaning with a tongue scraper every morning for 4 weeks, and then waited for 4 weeks. The delayed intervention group initially waited for 4 weeks, and then started tongue cleaning in the same way. Main outcome measures: We assessed the outcomes using the questionnaire on digestive power from Ayurvedic viewpoint, and the General Oral Health Assessment Index for OHRQoL. We estimated the effects of tongue cleaning using generalized estimating equations (GEE). We also conducted a sensitivity analysis, by comparing the changes in outcomes during the first 4 weeks of both groups. Results: Of 58 participants, 57 completed the study. In GEE analysis, tongue cleaning showed improvement in some components of Ayurvedic digestive power represented by fecal and body conditions. For example, the odds ratio for improvement of constipation was 2.80 (95% CI: 1.04–7.58). The General Oral Health Assessment Index score was significantly increased by 4.33 points (95% CI: 2.18–6.48) after tongue cleaning. In sensitivity analyses, the trends of the results were similar to the main GEE analyses. Conclusions: Tongue cleaning may be an effective method to improve digestive power and OHRQoL.